Using Microsoft Teams for Teaching Writing in Junior High School - Putri, Eka Syahwalda (Universitas Negeri Surabaya, 2023)
COVID-19 pandemic causes all schools in Indonesia have to do online learning. In this case, Microsoft Teams is one of the platforms used by schools to hold online teaching-learning process. This research aimed to describe the implementation and teachers’ obstacles while using Microsoft Teams for teaching writing in junior high school. It focused on the descriptive text material which must be learned by the seventh-grade students. This qualitative research took place in one of the public schools in Surabaya by involving two English teachers who teach seventh-grade students and knows how to operate Microsoft Teams for the teaching-learning process. Based on the observation and interview results, Microsoft Teams provides great features to support the teaching process. It also found that there are some obstacles that should face by the teacher such as cannot reach out to the students who have lost connection with Microsoft Teams because of changing the phone numbers, lack of interaction with the students, and have a bad internet connection.